2010
DOI: 10.1055/s-0030-1248279
|View full text |Cite
|
Sign up to set email alerts
|

Screening-Instrument für die Borderline-Persönlichkeitsstörung. Diagnostische Effizienz der deutschen Version des McLean Screening Instrument for Borderline Personality Disorder

Abstract: Borderline personality disorder (BPD) is a life-threatening mental disorder. To date, there is no German screening tool available. To examine the psychometric properties of a German version of the McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD). A heterogeneous outpatient sample (N=168) was used to examine discriminatory ability, diagnostic efficiency as well as indicators for internal consistency and convergent validity. The area under the curve was AUC=0.90 (CI 95%: 0.85 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…The MSI consists of 10 true–false self-rated items assessing common symptoms of borderline personality disorder. The German translation of the MSI has demonstrated good psychometric properties (Kröger, Vonau, Kliem, & Kosfelder, 2010; in the current study, α = .81, 95% CI [.73, .87]). If participants scored above the cut-off of 7 (Kröger et al, 2010) on the MSI, the borderline personality disorder section of the SCID-II (Fydrich, Renneberg, Schmitz, & Wittchen, 1997) was conducted to test for possible borderline personality disorder.…”
Section: Methodsmentioning
confidence: 62%
“…The MSI consists of 10 true–false self-rated items assessing common symptoms of borderline personality disorder. The German translation of the MSI has demonstrated good psychometric properties (Kröger, Vonau, Kliem, & Kosfelder, 2010; in the current study, α = .81, 95% CI [.73, .87]). If participants scored above the cut-off of 7 (Kröger et al, 2010) on the MSI, the borderline personality disorder section of the SCID-II (Fydrich, Renneberg, Schmitz, & Wittchen, 1997) was conducted to test for possible borderline personality disorder.…”
Section: Methodsmentioning
confidence: 62%
“…The MSI-BPD (Kröger, Vonau, Kliem, & Kosfelder, 2010 [German translation by S. Hörz]; Zanarini et al, 2003) is a 10-item screening instrument for borderline personality with a dichotomous answer format (yes/no); α current sample = .83.…”
Section: Study 2: Validity Of the Pni: Expanding The Nomological Netmentioning
confidence: 99%
“…An ROC curve is created when the true positive rate (sensitivity) is plotted against the false positive (1 − specificity) rate. The area under the curve (AUC) can then be calculated using the nonparametric trapezoid method (Hanley & McNeil, 1982) that yields an index of accuracy, which has been used in several other studies to establish criterion validity (Fombonne, 1991;Thapar & McGuffin, 1998). A measure is thought to have low diagnostic accuracy if its AUC is below .7, moderate accuracy from .7 to .9, and high accuracy when greater than .9 (Swets & Pickett, 1982).…”
Section: Convergent Validity With Dimensional and Categorical Measures Of Bpdmentioning
confidence: 99%
“…Gardner and Qualter (2009) found that the MSI-BPD correlated highly with other BPD screening tools in a mixed community and student sample, and reported that confirmatory factor analysis suggested that the MSI-BPD is an appropriate measure for assessing BPD as a global construct. Since initial validation of the MSI-BPD, the instrument has been translated to other languages for international use (e.g., Kröger, Vonau, Kliem, & Kosfelder, 2010), and has demonstrated promise for use in both population-based treatment studies and primary care settings for clinical and nonclinical adult samples (Gardner & Qualter, 2009).…”
mentioning
confidence: 99%